The Ability of Ferns to Accumulate Heavy Metals (Hg, Pb And Cd) In The Waters of The Gorontalo River - muhamad iksan; La Aba Aba; Kusrini Kusrini (International Journal of Applied Biology, 2019)
Sustainable  development  can be caused by more human’s activity. This activity, it will have an impact on the surrounding  environment  which  can  disrupt  the  stability  of  the  ecosystem,  one  of  which  is  the  river  water ecosystem.  The  research  aims  to  determine  the  ability  of  ferns  in  accumulating  heavy  metals  so  that  they  can  be  used  as  indicators  of  the  depletion  of  river  waters  ecosystem  environments  and  can  be  used  as  fitoremediant areas  of  waters  which  accumulate  heavy  metals.  This  research   is  descriptive  quantitative.  Retrieval  of  initial  data or  sample  in  this  study  used  survey  methods  and  random  sampling  techniques,  testing  samples by  using   the Ranger  X-ray  Flourenciece  (XRF)  method.  Based  on  the  results  of  the  study  that, ferns  can  accumulate  heavy metals,  the  parts  that  accumulate  are  located  below  the  root  surface  and  above  the  soil  surface,  namely stems and  leaves.  In  the  roots  have  more  amount  in  accumulating  heavy  metals  than  in  the  stem  and  leaves, this  is because  the  metal  is  indicated  on  the  soil.  From  these  results,  it  can  be  concluded  that  ferns  can  be used as water  purification  plants  in  river  ecosystems  that  are  indicated  by  heavy  metals.